1978
DOI: 10.1007/bf01349582
|View full text |Cite
|
Sign up to set email alerts
|

Physician and patient assessment of ambulatory care in a university facility

Abstract: Physicians are a largely untapped resource for evaluating medical care delivery in an ambulatory care facility. This study includes the attitudes of physicians in assessing care at the Northwestern University Medical School Clinics (NUMSC). A self-administered questionnaire was mailed to all clinic chiefs, attending physicians, and resident physi--cians who had worked in the clinics during the summer of 1973. Using a similar questionnaire, personal interviews were conducted with a sample of patients in the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…It appears that physicians were more critical of the quality of their communication than patients. This finding is consistent with other studies 3,10–12,15 . The correlation between patients’ and physicians’ ratings was not high, which indicates that patients and physicians actually judged the consultation differently.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It appears that physicians were more critical of the quality of their communication than patients. This finding is consistent with other studies 3,10–12,15 . The correlation between patients’ and physicians’ ratings was not high, which indicates that patients and physicians actually judged the consultation differently.…”
Section: Discussionsupporting
confidence: 92%
“…Although some studies have considered physicians’ satisfaction with provided care, 1,3–11 only a few have explicitly examined whether patients’ and physicians’ visit‐specific satisfaction are congruent 12–15 . The latter studies were conducted in general practice 12–14 and an internal medicine outpatient clinic 15 .…”
mentioning
confidence: 99%
“…This finding was consistent with client satisfaction studies related to ambulatory-care services and physician care (Goyne et al, 1973;Hilton et al, 1984;Orden et al, 1978;OrthoGomer et al, 1979).…”
Section: Discussionsupporting
confidence: 91%
“…The authors, however, reported that the literature revealed no major variances in results when two different methods were used for survey (Orden et al, 1978). In another study on client satisfaction, ambulatory-care physicians perceived that clients would be less satisfied with services than the clients' actual reports indicated.…”
Section: Client Satisfaction With Ambulatory-care Servicesmentioning
confidence: 83%
See 1 more Smart Citation